Sistem Informasi Pendataan UMKM di Dinas Koperasi, UKM, Perindustrian dan Perdagangan Sumba Tengah Berbasis Web - Ferdinandus Kaledi Wawu; Adelbertus Umbu Janga; Mitra Permata Ayu (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
The web-based MSME Data Collection Information System at the Central Sumba Cooperative, SME, Industry and Trade Office aims to improve efficiency in managing data and information related to Micro, Small and Medium Enterprises (MSMEs) in the Central Sumba region. This system is designed to simplify the process of data collection, monitoring, and reporting on MSMEs, which was previously done manually. Using web-based technology, this system can be accessed by MSME managers, local governments, and other relevant parties in order to accelerate data-driven decision making. This information system provides MSME data collection features, structured data storage, MSME development reporting, and statistical analysis that can assist in policy planning to improve the competitiveness and welfare of MSMEs in Central Sumba. With this system, it is hoped that it can support the development of the MSME sector in Central Sumba to be more transparent, accurate, and integrated.